The Influence of Teachers Agreeableness and Openness to Experience on Secondary School Students' English Language Academic Achievement in Ogoja Education Zone of Cross River State, Nigeria - Nkomo, Ntu N.; Ochiche, Ushie Peter; Akpan , Emmanuel Mendie (Journal of Education and Practice, 2022)
Purpose: The study sought to determine the extent to which teacher's agreeableness and teachers' openness to experience influence secondary school students' English language academic achievement in Ogoja education zone of Cross River State, Nigeria. To carry out this study, two null hypotheses were formulated derived from the two research questions that were posed to guide the study. Methodology: The research design adopted for the study was ex-post facto design. The stratified random sampling technique was used to select 800 out of 7,196 SS 1&2 students who participated in the study. A pilot trial test of the research instrument titled teacher's personality traits questionnaire (TPTQ) was administered to 50 SS 1&2 students in Calabar education zone. The analysis of the questionnaire yielded reliability coefficients ranging from .703 to .782 while that of the achievement test was .778. The data obtained were coded and analysed with the two (2) null hypotheses tested at .05 level of significance using simple linear regression. Results: The results showed that Teacher's agreeableness does positively and significantly influence secondary school student's English language academic achievement. It also revealed that there is a significant positive influence of teachers' openness to experience on secondary school student's English language academic achievement in Ogoja Education Zone of Cross River State, Nigeria. Unique Contribution to Theory, Policy and Practices: It was therefore recommended that teachers should expound their commitment by building caring relationships with students such that will make them approachable. It was equally recommended also that English teachers should be friendly and disposed at any time to meet the needs of the students academically.